Digital Mathematics Learning Environments for Enhancing Conceptual Understanding and Technological Pedagogical Competence among Pre-Service Mathematics Teachers: A Literature Review - Agusalim Juhari (International journal of technology and education research, 2026)
The rapid development of digital technology has transformed mathematics learning environments by enabling dynamic visualization, interactive exploration, multiple representations, collaborative learning, and immediate feedback. In mathematics teacher education, digital learning environments are not only used to support students’ understanding of mathematical concepts but also to prepare pre-service teachers to integrate technology meaningfully into future teaching practices. This article aims to examine the role of digital mathematics learning environments in enhancing conceptual understanding and technological pedagogical competence among pre-service mathematics teachers. This study used a literature review approach by synthesizing relevant theoretical and empirical studies on digital mathematics learning environments, GeoGebra, technology-enhanced mathematics learning, digital learning ecosystems, conceptual understanding, and technological pedagogical content knowledge. The review was guided by four questions: what are the characteristics of digital mathematics learning environments, how do they contribute to conceptual understanding, how do they support technological pedagogical competence among pre-service mathematics teachers, and what challenges affect their implementation. The findings indicate that digital mathematics learning environments can support conceptual understanding through visualization, manipulation of mathematical objects, multiple representations, exploratory tasks, collaborative interaction, and feedback. In teacher education, such environments also strengthen technological pedagogical competence through technology-rich learning experiences, digital task design, microteaching, reflection, and TPACK development. However, their effectiveness depends on meaningful task design, teacher educator competence, infrastructure readiness, students’ digital adaptation, and assessment models that capture both conceptual and pedagogical dimensions. This review concludes that digital mathematics learning environments should be positioned as pedagogical ecosystems rather than merely as technological tools.